2022
DOI: 10.1016/j.psj.2021.101569
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza outbreaks: evaluating the efficacy of cleaning and disinfection of vehicles and transport crates

Abstract: In 2021, France faced large avian influenza outbreaks, like in 2016 and 2017. Controlling these outbreaks required the preventive depopulation of a large number of duck farms. A previous study in 2017 showed that the quality of decontamination of trucks and transport crates used for depopulation was often insufficient. A new study was then set up to evaluate cleaning and disinfection ( C&D ) of trucks and crates used for duck depopulation and whether practices had changed since 2017. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, one study has shown that AIV was detected inside, outside of, and downwind from infected duck and chicken facilities in France [ 26 ]. To prevent the infections of IBV and AIV in poultry farms, it is important to treat the environment, such as surfaces and air, using proper disinfectants with adequate concentration and in an appropriate way to effectively reduce major or residual viral contamination [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study has shown that AIV was detected inside, outside of, and downwind from infected duck and chicken facilities in France [ 26 ]. To prevent the infections of IBV and AIV in poultry farms, it is important to treat the environment, such as surfaces and air, using proper disinfectants with adequate concentration and in an appropriate way to effectively reduce major or residual viral contamination [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle washing was moderately important as measured by both LOOCV and BMA. This finding of moderate importance may be an artifact of the limitations of a survey-based approach; effectiveness of cleaning can be difficult to measure based on visual inspection ( 49 ). Notably, multiple vehicle wash-related variables were univariately significant ( p ≤ 0.20), including washing of feed trucks, egg trucks, washing truck tires, and having a permanent vehicle washing station.…”
Section: Discussionmentioning
confidence: 99%
“…Decontamination of vehicles may be impaired by the presence of rough surfaces and hidden areas where organic material can build up (Baker et al., 2017 ). When vehicles are not properly cleaned and disinfected prior to loading of animals (Arthur et al., 2008 ; Weber and Meemken, 2018 ; Huneau‐Salaün et al., 2020 , 2022 ), exposure to ARB/ARGs in the following transport can occur. Within 2 h after experimental exposure to contaminated areas, Salmonella can be found in the caecal content of broilers or pigs (Rigby and Pettit, 1980 ; Boughton et al., 2007a ).…”
Section: Assessmentmentioning
confidence: 99%
“…are better controlled. Decontamination can be improved by an additional disinfection stage after washing (Davies and Wray, 1994) and strict segregation of pre and post washing airspaces (Huneau-Sala € un et al, 2022). As with vehicles, Dzieciolowski et al ( 2022) reported that hot air drying of crates after washing and disinfection could improve reduction of Enterobacteriaceae from just over 2 logs to nearly 3.5 logs.…”
Section: Mitigation Measures After Transportmentioning
confidence: 99%